PPARγ and Cognitive Performance - d’Angelo, Michele (Int J Mol Sci, 2019)
Recent findings have led to the discovery of many signaling pathways that link nuclear receptors with human conditions, including mental decline and neurodegenerative diseases. PPARγ agonists have been indicated as neuroprotective agents, supporting synaptic plasticity and neurite outgrowth. For these reasons, many PPARγ ligands have been proposed for the improvement of cognitive performance in different pathological conditions. In this review, the research on this issue is extensively discussed.